2007
DOI: 10.1128/iai.01392-06
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Intestinal Lymphoid Tissue Provides a Productive Port of Entry for Salmonella enterica Serovar Typhimurium

Abstract: Oral infection of mice with Salmonella enterica serovar Typhimurium results in the colonization of Peyer's patches, triggering a vigorous inflammatory response and immunopathology at these sites. Here we demonstrate that in parallel to Peyer's patches a strong inflammatory response occurs in the intestine, resulting in the appearance of numerous inflammatory foci in the intestinal mucosa. These foci surround small lymphoid cell clusters termed solitary intestinal lymphoid tissue (SILT). Salmonella can be obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…These data argue that the location and number of ILFs is determined developmentally and cannot be altered by inflammation or infection. However, the final maturation and organization of ILFs is dependent on microbial stimuli and can even be enhanced by infection with pathogenic bacteria (128). Together, these data demonstrate that the development of ILFs has some characteristics in common with the development of ectopic lymphoid follicles, but other characteristics of secondary lymphoid organs.…”
Section: Exceptions To the Paradigm Of Secondary Lymphoid Organ Develmentioning
confidence: 53%
“…These data argue that the location and number of ILFs is determined developmentally and cannot be altered by inflammation or infection. However, the final maturation and organization of ILFs is dependent on microbial stimuli and can even be enhanced by infection with pathogenic bacteria (128). Together, these data demonstrate that the development of ILFs has some characteristics in common with the development of ectopic lymphoid follicles, but other characteristics of secondary lymphoid organs.…”
Section: Exceptions To the Paradigm Of Secondary Lymphoid Organ Develmentioning
confidence: 53%
“…As in the case of PPs, a follicle associated epithelium with M cells is present on the lumen facing side of ILFs. Uptake of pathogens including S. typhimurium, leads to the formation of germinal centers (GCs) in mature ILFs [64][65][66]. Interestingly, it was found that the presence or absence of GCs in ILFs did not influence the active class switching of naïve B cells to active IgA secreting B cells [67].…”
Section: Antigen Uptake In the Gutmentioning
confidence: 98%
“…Therefore, Salmonella most likely persists at another gastrointestinal site, which we could not detect even by sensitive culture methods. One potential site would be solitary intestinal lymphoid tissues (SILT), poorly studied lymphoid cell clusters that are known to be infected with Salmonella following oral infection (18). Such a low level of persistence is more rapidly manifested in adenectomized mice, which lack the protective firewall of the MLNs to reduce the systemic spread of bacteria after the removal of antibiotics.…”
Section: Discussionmentioning
confidence: 99%